Pengembangan Model Pembelajaran Inovatif Bagi Calon Guru Sekolah Dasar - Adsar (CV. SINAR HOWUHOWU, 2025)
This study aims to develop an innovative learning model that can be implemented in the education of elementary school teacher candidates. Using a research and development (R&D) approach, this study designs a learning model that integrates problem-based learning, project-based learning, and the use of digital technology to enhance student engagement and pedagogical competence among teacher candidates. The research stages include needs analysis, model design, and classroom implementation. The results show that teacher candidates were able to adopt and implement the learning model effectively, improving their skills in designing and delivering more creative and interactive lessons. However, challenges related to limited facilities and varying levels of technological proficiency remain as barriers. The study suggests the need for further training and mentoring for teacher candidates to maximize the use of this innovative learning model. The developed model is expected to serve as a reference for enhancing the quality of teacher education and enriching the learning experience of elementary school students.